The Use of Murine Models for Studying Mechanistic Insights of Genomic Instability in Multiple Myeloma - Vlummens, Philip; De Veirman, Kim; Menu, Eline; De Bruyne, Elke; Offner, Fritz; Vanderkerken, Karin; Maes, Ken (Frontiers in Genetics, 2019)
Multiple myeloma (MM) is a B-cell malignancy characterized by the accumulation of clonal plasma cells in the bone marrow. In normal plasma cell development, cells undergo programmed DNA breaks and translocations, a process necessary for generation of a wide repertoire of antigen-specific antibodies. This process also makes them vulnerable for the acquisition of chromosomal defects. Well-known examples of these aberrations, already seen at time of MM diagnosis, are hyperdiploidy or the translocations involving the immunoglobulin heavy chain. Over recent years however, novel aspects concerning genomic instability and its role in tumor development, disease progression and nascence of refractory disease were identified. As such, genomic instability is becoming a very relevant research topic with the potential identification of novel disease pathways. In this review, we aim to describe recent studies involving murine MM models focusing on the deregulation of processes implicated in genomic instability and their clinical impact. More specifically, we will discuss chromosomal instability, DNA damage and repair responses, development of drug resistance and recent insights into the study of clonal hierarchy using different murine MM models. Lastly, we will discuss the importance and the use of murine MM models in the pre-clinical evaluation of promising novel therapeutic agents.